Uji Pupuk Slow Release Urea Dirakit dari Berbagai Bahan Polimer terhadap Pertumbuhan dan Hasil Bawang Merah Tiron pada Tanah Sawah Purwosari - Azizah, Amatullah Nurul; Widyasunu, Purwandaru; Rokhminarsi, Eny (Proceedings Series on Physical & Formal Sciences, 2021)
This research aims to determine 1) the effect of four formulas on slow release urea on the growth and yield of shallot plant at Purwosari village and 2) formula of slow release urea that have the best growth and yield of shallot plant at Purwosari village. The research was conducted in November 2019 untill Maret 2020 The research was conducted at the ex-paddy fields of Purwosari village, Baturraden District, Banyumas Regency and Research Laboratory, Jenderal Soedirman University. Research in the form of non-factorial field experiments using RAKL with five treatments repeated five times. The formula of each treatment includes: F0 = NPK (Urea, SP-36, and KCl), F1 = 70% urea + 6% chitosan + 24% humic acid, F2 = 70% urea + 10% Azolla microphylla + 10% gondorukem + 10% humic acid , F3 = 60% urea + 10% Azolla microphylla + 10% montmorillonite + 10% gondorukem + 10% humic acid, and F4 = 56% urea + 3% humic acid + 24% zeolite + 11% tapioca flour + 6% gondorukem. The observed variable including growth and yield components of shallot. The variable of growth including the height of plant, the number of leaves, the weight of fresh plant of clump-1, the weight of fresh plant of effective plot, the weight of dry plant of clump-1, the weight of dry plant of effective plot, and the number of clump-1 bulbs. The yield components of shallot is a bulbs. Result of the research showed that the best formula for plant growth and yield of shallot plant is F2. The growth and yield of shallot produced by F4 is always lower than in the control treatment (F0). Farmers can fertilize less and optimize nitrogen uptake by plants with application of slow release of urea.